Science of wealth - "Carter, C F" (London, 1960)
Here are three of the most important financial books ever written in one volume. All three of these books cover how to become rich, from slightly different angles. Following the advice that is laid out clearly in these books will help you live a happier more wealthy life. Success is right around the corner. He was a profound influence on Michael Losier and James Arthur Ray. Without Wattles "Science Of" trilogy, there never would have been books such as The Laws of Attraction, The Science of Success, and the Power of Positive Thinking. Now you can go directly to the source! In Think and Grow Rich Napoleon Hill researched more than forty millionaires to find out what made them the men that they were. In this book he imparts that knowledge to you. Once you've read this book you will understand what gives certain people an edge over everyone else. After reading this book you'll be the one with an edge. It's time to stop wondering what it's like to be rich and start knowing. The Master Keys System will not only outline how important positive thinking is, it will guide you through practical lessons that will make it easy for you to change your entire way of thinking. Charles F. Haanel has mapped out a twenty four lesson program that, when followed, realizes tremendous results.
Keywords: Economics